Productivity in electricity retail after market liberalisation: Analysing the effects of ownership and firm's governance structure - Caroline Stiel; Astrid Cullmann; Maria Nieswand (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper, which is one of the first to estimate productivity in retail electricity for a European country after liberalisation, analyses the effect of ownership and governance structure by using a unique dataset of German electricity retailers from 2003 to 2012. An innovative service production function for the retail sector is derived with labour and external services as the main inputs. A structural model is used with a proxy function for productivity to overcome the endogeneity of input choice. Ownership is controlled for in the law of motion for productivity. The results of the dataset used to validate the model show that firm-level productivity did not increase after 2008 and that ownership had no effect on productivity. The results provide useful insights into the link between ownership and productivity in modern public enterprises after liberalisation.
Keywords: D24; L11; C23; L94; 330; Productivity; Structural Production Function; Electricity Retail; Ownership; Governance